Response of the Magnetospheric Convection Electric Field (MCEF) to Geomagnetic Storms During the Solar Cycle 24 Maximum Phase - Bazié Nongobsom; Kaboré Salfo; Guibula Karim; Ouattara Frédéric (International Journal of Geophysics)
The present work focuses on the variability of the magnetospheric convection electric field (MCEF) during geomagnetic storms generated by coronal mass ejections (CMEs). The aim of the study was to analyze the response of the MCEF to geoeffective CMEs occurring during the maximum phase of Solar Cycle 24. A total of eight storms were selected on the basis of their intensity with respect to the Dst (disturbance storm time) and Kp (planetary geomagnetic index) indices. We examined the variations in solar wind parameters (VSW (solar wind speed), PSW (plasma pressure), and interplanetary magnetic field (IMF) Bz) and geomagnetic indices (Sym-H (symmetric horizontal) and auroral electrojet (AE)) during these storms. We analyzed the time lag between the MCEF and AE, Sym-H, and IMF Bz using a cross-correlation analysis. The study shows that CMEs arriving in the magnetosphere at a speed of 800–960 km/s induce a change in MCEF of 0.95–1.29 mV/m in the initial phase, and those transiting at a speed of 520–651 km/s induce a change in MCEF of 0.78–0.91 mV/m. During storms associated with CMEs arriving at a speed of 520–651 km/s, a change in IMF Bz of 1 nT is associated with a change in MCEF of about 0.05 mV/m. During those associated with CMEs transiting at a speed of 800–960 km/s, each 1 nT change in IMF Bz corresponds to a change in MCEF of about 0.07 mV/m. Variations in the MCEF follow those in the AE index in 88% of the storms studied, with a time lag ranging from 9 to 79 min. They precede those of the ring current index (Sym-H) in 50% of the cases analyzed, with a time lag varying from 49 to 742 min. These results provide us with some information on the complete evolution of geomagnetic storms, with a view to better prediction.